Analysis of P2P file sharing network's credit system for fairness management - Li, Yunzhao; Gruenbacher, Don M. (IEEE, 2010)
Fairness is an important management issue for peer-to-peer file sharing systems. In this paper, we study the credit system of the P2P file sharing network eMule (http://www.emule-project.net) through a simple queueing network model. Numerical analysis and experimental results show that this local credit strategy could effectively deal with free riders and provide fairness for the system during a single file exchange. Using this model, we also investigate different management strategies for dealing with the newcomer fairness issue. We propose a simple, private history-based scheme to balance the fairness between two types of newcomers.
Keywords: Peer-to-peer file management systems; P2P; eMule; Fairness; Newcomer; Credit system